Deformation detection for Iskandarnet - Lim, Meng Chan (2012)
Tragedies and disasters in the past have shown the threats that are associated with large construction projects. A timely identification of precursory movements may save lives and minimise collateral damage. An advanced global positioning system (GPS) continuously operating reference station network known as ISKANDARnet is operated continuously to detect deformations in Iskandar, State of Johor, Malaysia. In this study, three GPS continuously operating reference stations from the ISKANDARnet were used as the object stations along four nearby international GNSS service stations (NTUS, XMIS, COCO and PIMO) used as reference stations. The GPS data were streamed and processed by a GPS processing software module, Bernese processing engine. A deformation analysis module was developed using the MATLAB programming language to carry out continuous two-epoch analyses. The development also involves the implementation of the iteratively weighted similarity transformation method and a final S-transformation to analyse the GPS data. By applying these techniques, unstable object points were identified within the monitoring network and accurate displacement vectors were computed. The time-based variation of the displacements was shown in this paper. Test results showed that the system performed satisfactorily.